1992
DOI: 10.1021/ic00049a027
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic reduction of carbon dioxide based on 2,2'-bipyridyl complexes of osmium

Abstract: The complex cis-[Os(bpy)2(CO)H]+ (bpy is 2,2'-bipyridine) has been found to be an electrocatalyst for the reduction of C02 in CH$N containing 0.1 M tetra-n-butylammonium hexafluorophosphate at glassy carbon or Pt electrodes. Under anhydrous conditions CO is the dominant product, but addition of water results in up to 22% formate anion. Kinetic parameters derived by digital simulation of cyclic voltammograms under electrocatalytic conditions are consistent with a rate-determining associative step (kl) in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 2 publications
2
31
0
Order By: Relevance
“…Although the spectrometer can be configured to scan to 27 000 cm-', the region past 22 000 cm-' is unreliable due to the low power of our visible source. Similar results were obtained for other selected nickel clusters (3)(4)(5)(6). Methods for increasing the sensitivity of the SEC response past 22 000 cm-' are being pursued.…”
Section: Wave Numbersupporting
confidence: 86%
See 3 more Smart Citations
“…Although the spectrometer can be configured to scan to 27 000 cm-', the region past 22 000 cm-' is unreliable due to the low power of our visible source. Similar results were obtained for other selected nickel clusters (3)(4)(5)(6). Methods for increasing the sensitivity of the SEC response past 22 000 cm-' are being pursued.…”
Section: Wave Numbersupporting
confidence: 86%
“…Infrared SEC studies on [Ni3(p3-CNR)(p3-I)(p2-dppm)3]+ (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) A distinguishing feature of the IR spectra for many of the isocyanide capped clusters 2-14 is the appearance of ttvo v(C=N) absorption bands, both in the solid state and in solution. Isotope labeling experiments confirmed that the appearance of two v(C=N) bands was a result of a Fermi resonance between the v(C=N) fundamental and the first overtone of the v(N-C(alky1)) fundamental (1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Progress has also been made on catalytic reduction of CO 2 to CO (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Both present a formidable challenge in chemical reactivity.…”
mentioning
confidence: 99%